Soluções tipo vórtex em teorias de gauge Chern-Simons-Maxwell-Higgs - Hoff da Silva, Julio Marny [UNESP] (2005)
In this work we make a systematic introduction to the concept of vortex solutions in ﬂat gauge theories. Such solutions are analyzed through the Bogomol'nyi's mechanism and the basic group of homotopy and are gotten for the models of abelian Higgs with and without Chern-Simons (CS) term, beyond a complete analyses including the Higgs model with CS and Maxwell's term